2014
DOI: 10.2319/072213-534.1
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngeal airway space, hyoid bone position, and head posture after bimaxillary orthognathic surgery in Class III patients:Long-term evaluation

Abstract: Objective: (1) To determine the effect of bimaxillary orthognathic surgery on pharyngeal airway, hyoid bone, and craniocervical posture in Class III bimaxillary surgery patients. (2) To evaluate short-term and long-term results. (3) To compare short-and long-term values. Materials and Methods: Twenty-six Class III adult patients treated with bimaxillary surgery were included in the study. Cephalometric records were taken before treatment (T1), before surgery (T2), and 5 months (T3), 1.4 years (T4), 3 years (T5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 27 publications
0
19
0
1
Order By: Relevance
“…Aydemir et al [21] reported no significant differences in the position of the hyoid bone between bimaxillary and mandibular setback surgery groups during a 1-year follow-up period. Efendiyeva et al [22] showed significant superior movement of the hyoid bone after bimaxillary surgery. The authors also found adaptation had occurred to the normal position in the 5-year follow-up.…”
Section: Discussionmentioning
confidence: 98%
“…Aydemir et al [21] reported no significant differences in the position of the hyoid bone between bimaxillary and mandibular setback surgery groups during a 1-year follow-up period. Efendiyeva et al [22] showed significant superior movement of the hyoid bone after bimaxillary surgery. The authors also found adaptation had occurred to the normal position in the 5-year follow-up.…”
Section: Discussionmentioning
confidence: 98%
“…Various studies report the importance of the head positioning in relation to the decrease in the expansibility of the upper respiratory tract 39,40 , since, although the forward head movement (flexion of the lower cervical spine while extending its upper portion) facilitates the entry of air, it impairs the biomechanical relationship between the flexor and extensor neck muscles. However, a systematic review conducted by Gurani et al 41 showed that literature on this subject is limited, of low quality, and there is little evidence available regarding the effect of head posture in the dimensions of upper respiratory tract.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, numerous articles have been published regarding the change of the posterior pharyngeal airway space after orthognathic surgery. 1 , 3 , 11 , 13 , 14 , 16 , 17 , 22 30 In addition, because obstructive sleep apnea accompanied by snoring symptoms has been recognized as an important preexisting factor causing many chronic diseases such as hypertension, coronary heart disease, and cerebral vascular disease, orthognathic surgery has been used as an ultimate tool for the correction of obstructive sleep apnea. 16 , 28 , 31 However, when we perform the mandibular setback surgery in prognathic patients, some patients with class III dentofacial deformities suffer from postoperative snoring and some degree of obstructive sleep apnea for the same reason.…”
Section: Discussionmentioning
confidence: 99%